"Чапаев" Дм. Фурманова - Бережной Александр Федосеевич (Массовая ист.-лит. библиотека, 1965)
Шмуцтит.: Массовая ист.-лит. б-ка Экземпляры: (20170406) / Инвентарный номер: 21870 / Цена: 0.19 / Сис.шифр: 8Р2(Фурамнов) / Авт.знак: Б48 / ББК: 8Р2(Фурамнов)